Physiological responses to agonist-antagonist superset resistance training - Fink, J.; Schoenfeld, B. J.; Sakamaki-Sunaga, M.; Nakazato, K. (Journal of Science in Sport and Exercise, 2021)
Purpose: To investigate the physiological responses to low-load, superset resistance training (two exercises for the agonist and antagonist muscles performed without rest between exercises) to failure using elastic bands. Methods: Twenty-three athletes were randomized to either a superset group (S, n = 12, average age: 19.8 ± 1.5 years) or a traditional set group (T, n = 11, average age: 20.1 ± 1.4 years). Strength, cross-sectional area (CSA) and muscular endurance of the biceps and triceps brachii were assessed before and after 8 weeks. Acute responses (muscle thickness) were measured during one testing session. Results: Muscle thickness of the biceps significantly increased in both T group (P < 0.05) and S group (P < 0.05) after a single bout of Training. The triceps did not show significant increases in either T group (P > 0.05) or S group (P > 0.05). Blood lactate also increased in both groups after one bout of training (T: from 1.3 ± 0.3 to 5.5 ± 2.4 mmol/L, S: from 1.4 ± 0.5 to 5.1 ± 1.5 mmol/L, P < 0.05). After 8-week training, both groups showed significant increases in the biceps (T: 13.2% ± 5.0%; S: 12.9% ± 7.3%, P < 0.05) and triceps (T: 9.5% ± 9.3%, S: 4.8% ± 4.1%, P < 0.05) without differences between groups. Increases in one repetition maximum for the bench press (7.8% ± 6.5%, P < 0.05) and maximal voluntary contraction for the arm extensors (9.3% ± 11.6%, P < 0.05) were observed for the T group only. Increases in muscular endurance were observed only in the S group for the bench press (26.0% ± 19.1%, P < 0.05) and the barbell curl (17.2% ± 16.6%, P < 0.05). Conclusions: Superset training may enhance muscular endurance while attenuating maximal strength gains. There does not appear to be a hypertrophic benefit to performing superset training, but it may provide a time-efficient strategy to achieve adaptations in muscle mass.